2021
DOI: 10.1155/2021/5561980
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aerobic Exercise on Rats with Hyperandrogenic Polycystic Ovarian Syndrome

Abstract: Hyperandrogenism is a key pathologic characteristic of polycystic ovarian syndrome (PCOS), and exercise can alleviate the accompanying inflammation and decrease the high androgen levels, but the mechanism is still unclear, so the purpose of this study is to explore the pathophysiologic characteristics of hyperandrogenic PCOS and the mechanism underlying its amelioration with aerobic exercise. Thirty-two female rats were randomly allocated to a normal control group (NC, n = 8), exercise control group (EC, n = 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 58 publications
2
9
0
Order By: Relevance
“…It has been suggested that high leptin in PCOS may interfere with the development of the mature oocyte and ovarian steroidogenesis, contributing to ovulatory dysfunction and infertility ( 20 , 21 ). Moreover, hyperleptinemia may interact with hyperandrogenemia and chronic low-grade inflammation in PCOS, forming a vicious circle in PCOS ( 22 ). Collectively, these findings indicate that leptin might play a role in the occurrence and development of PCOS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that high leptin in PCOS may interfere with the development of the mature oocyte and ovarian steroidogenesis, contributing to ovulatory dysfunction and infertility ( 20 , 21 ). Moreover, hyperleptinemia may interact with hyperandrogenemia and chronic low-grade inflammation in PCOS, forming a vicious circle in PCOS ( 22 ). Collectively, these findings indicate that leptin might play a role in the occurrence and development of PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest that androgens may be involved in the pathogenesis of elevated serum leptin levels, and that leptin may further aggravate the PCOS phenotype, as a secondary response to the increase in the androgen levels. High leptin levels can inhibit aromatase activity, which is a key enzyme in the conversion of androgens to estradiol, further aggravating hyperandrogenemia, which affects follicle growth and development, resulting in ovulation dysfunction ( 22 ). These findings suggest that the mechanism of leptin involvement in PCOS pathology is related to androgen.…”
Section: Discussionmentioning
confidence: 99%
“…This may suggest that Leptin resistance in PCOS patients may be possibly mediated by Sam68, an RNA-binding protein that is widely expressed in the body and has signaling functions ( 81 ). A study aiming to illustrate the effects of aerobic exercise on PCOS rats with HA showed the effect of Leptin on inflammation in PCOS ( 82 ). In this study, the researchers divided the study subjects into normal control group with or without aerobic exercise and PCOS group with and without aerobic exercise (called NC, EC, PC, and PE group, respectively), and they were surprised to find that levels of TNF-α, IL-6, and Leptin were reduced in the PE group compared to the PC group.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, they speculated that aerobic exercise improved the inflammatory status of PCOS by reducing Leptin resistance. Aerobic exercise reduces internal inflammation by reducing Leptin resistance ( 82 ), and high-intensity interval training (HIT) reduces circulating Leptin levels in obese women and adolescents (both men and women) with risk factors for type 2 diabetes ( 83 , 84 ). But things change when it comes to the obese PCOS ( 85 ).…”
Section: Methodsmentioning
confidence: 99%
“…These changes correlated with a reduced serum leptin and the ratio of leptin to high-molecular-weight adiponectin [ 155 ]. Regarding exercise effects on hormonal outcomes, in murine models, a 15-day aerobic training has proved to be useful in decreasing inflammation and restoring the hormonal balance acting on levels of leptin, testosterone, estradiol, FSH, AMH, TNF-α, IL-6 and free fatty acids (FFA) [ 156 ]. Exercise positively affects the hormonal profile also in women: both continuous and intermittent aerobic training have been demonstrated to be useful in reducing circulating levels of testosterone as well as obesity parameters [ 157 ].…”
Section: Exercise Interventions In Pcos Womenmentioning
confidence: 99%